Effect of arrangement distances on stiffness of shear-tension mode in timber-to-timber connections with inclined screws. (3rd January 2022) - Liu, Yifan; Yao, Ziyin; Wang, Feibin; Huang, Hui; Que, Zeli
Highlights: Arrangement distances effect in timber-to-timber connections with inclined screws. The stiffness of the joints were quantified using the EEEP model. The estimation equation for the stiffness of the joint was proposed. Abstract: The effects of arrangement distances on stiffness in timber structure connections with inclined self-tapping screws were investigated in this study. Under the conditions of five end distances (ED-6D, ED-10D, ED-14D, ED-18D, and ED-22D) and four spacings (S-4D, S-8D, S-12D, and S-16D), shear-tension tests were conducted on the timber structure connections with inclined self-tapping screws, and the stiffness and other properties of the connections were evaluated. Based on the experimental data, the effects of the arrangement distances on the stiffness of the joints were quantified using the equivalent energy elastic–plastic model. The results showed that the arrangement distances had a certain impact on the yield mode and load-carrying capacity of the joints. As the end distance increased, the initial stiffness and ductility coefficient decreased. As the spacing increased, the initial stiffness of the connections increased. The estimation equation for the stiffness of the joint was proposed by comparing the end distances and spacings of the joint.